A Reversible Liquid Organic Hydrogen Carrier System Based on Methanol‐Ethylenediamine and Ethylene Urea. (6th March 2019) - Xie, Yinjun; Hu, Peng; Ben‐David, Yehoshoa; Milstein, David
Abstract: A novel liquid organic hydrogen carrier (LOHC) system, with a high theoretical hydrogen capacity, based on the unpresented hydrogenation of ethylene urea to ethylenediamine and methanol, and its reverse dehydrogenative coupling, was established. For the dehydrogenation only a small amount of solvent is required. This system is rechargeable, as the H2 ‐rich compounds could be regenerated by hydrogenation of the resulting dehydrogenation mixture. Both directions for hydrogen loading and unloading were achieved using the same catalyst, under relatively mild conditions. Mechanistic studies reveal the likely pathway for H2 ‐lean compounds formation.